Pretreatment of Sludge Milk Waste as Source Of Composting using Microbes - S. R. Juliastuti; Rian Setya Budi; Taufiqurrusydi Taufiqurrusydi (IPTEK Journal of Proceedings Series, 2014)
Anorganic fertilizer applicatio in high concentration causes damaging in agriculture field. An alternative way to protect the soil, is using organic fertilizer (compost). Sludge milk waste as souce of composting can be used, but it has high lipid content and causes hardening on composting process. Using combination microbes such as Rhizopus oligosporous (R. oligosporous) and Aspergillus niger (A. niger) in pretreatment of sludge milk waste can cause reducing of lipid content.Objective of this research is to know the influence of Rhizopus oligosporous (R. oligosporous) as anaerobic fermentation microorganism and Aspergillus niger (A.niger) as aerobic fermentation microorganism of sludge milk waste pre-treatment for further composting process, and to compare composting products against technical requirement organic compost used. The research method used is the anaerobic fermentation with addition of Rhizopus oligosporous and aerobic fermentation with Aspergillus niger. Process variables were 100 ml R. oligosporous and A. niger /3 kg sludge waste (3,33% v/w), 200 ml R.oligosporous and A. niger /3 kg sludge waste (6,67%v/w), and 300 ml R.oligosporous and A. niger /3 kg sludge waste (10%v/w) during incubation period of 72 and 96 hours. Process was continued through composted the pretreatment sludge by adding the biofertilizer and bone powder. After composting of pretreatment waste then Carbon, kalium, lipid, nitrogen, phosphate and water content were analyzed. Temperature and pH were also monitored. Results of this research shows that R. oligosporous and A. niger can reduce lipid content of sludge milk waste. The best variable is A. niger 6,67 % v/w with incubation period of  96 hours and can be proved with the lipid content of 10,44 %  and reducing of lipid content per cell of microorganism as 0,00036 ppm. Composting process has enhanced 1,57 % N, 5,16 % P and 1,2% K. This compost were in accordance with the technical requirements of organic fertilizer in Indonesia.